Bibliometric Analysis and Research Management - Mattens, W.C.M; Chung, Nguyen Huu Thanh; Duc, Nguyen Huu (VNU Journal of Science: Policy and Management Studies, 2015)
Traditional research managements were mostly driven by expert opinions (i.e. bottom-up up decision making system). In the last ten years, however, citation metrics provided by search systems for scholarly literature, like Web of Knowledge (Thomson Reuters), Scopus (Elsevier) and Google Scholar gain interest in boardrooms of research laboratories and universities. This bibliometric analysis can develop to serve research managements and science and technology strategy building. This paper provides and discusses some examples of such citation metrics and methodology of identifying and ranking research fronts. As a result,100 hottest world research fronts are introduced. The corresponding situation is reported for Vietnam and proposals for changes in research managements, policies and decision making are suggested for Vietnam and other developing countries. Keywords: Bibliometric analysis, research management, research fronts, innovation prediction.